The association between folic acid supplementation, maternal folate during pregnancy and intelligence development in infants: a prospective cohort study - Shaokang Wang; Jie Wei; Di Wang; Li Hua; Da Pan; Lingmeng Fu; Jin Yang; Guiju Sun (Food Science and Human Wellness)
Objective: The study aimed to explore the association between folic acid supplementation, maternal nutritional levels during pregnancy and intelligence development of infants. Method: This was a prospective cohort study, mothers and their offspring in Jurong Maternal and Child Health Hospital were followed up through pregnancy up to 1 year. The basic information of pregnant women was obtained through questionnaire survey, including pregnancy lifestyle, marital status, vitamin and mineral supplements during pregnancy. Blood samples of pregnant women were collected on admission, serum folate, vitamin B12 and homocysteine concentrations were determined. Maternal postpartum colostrum was collected and the concentrations of folate and vitamin B12 in colostrum were determined. Pregnant women (n = 478) and their corresponding infants were followed up and the Developmental Screen Test scores were recorded at 1,3,6,8 and 12 months of age. Results: Compared with the normal group, infants in the low serum folate group had a score of 0.12 points lower in the intellectual energy zone (95% CI: -0.23 – -0.01, P = 0.04), and infants with the high homocysteine level scored 1.30 points lower than the lower-level group (95% CI: -2.52 – -0.08, P = 0.04). In the colostrum low-vitamin B12 level group, infants scored 0.10 points lower (95% CI: -1.84 – -0.02, P = 0.02) in the social adaptation zone compared to the normal group. Conclusion: In conclusion, folic acid supplementation in the pre-pregnancy supplementation group and the post-pregnancy supplementation group may be not associated with infant mental development. In addition, maternal folate and homocysteine may be related to the intellectual development of infants. The level of vitamin B12 in colostrum may be associated with infants’ social adaptive capacity. This result may be caused by individual differences in folate and homocysteine metabolism in pregnant women.